1999
DOI: 10.1053/joca.1998.0199
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating effect of diacerein on TGF-β1 and β2 expression in articular chondrocytes cultured with and without interleukin-1

Abstract: The results suggest that diacerein effects on matrix synthesis and turn-over previously reported in cultured articular chondrocytes might be explained in part by the ability of the drug to enhance TGF-beta1 and TGF-beta2 expression in these cells. This mechanism of action may account for the potential disease-modifying properties of diacerein and might give clues as to how future anti-osteoarthritic drugs should be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…At the post-membrane level, diacerein inhibits the release of inflammatory and cartilage-degrading factors, inhibiting the activation of nuclear factor-kappa B [18]. It stimulates the production of cartilage growth factors such as transforming growth factor-beta and cartilage components, even in the presence of IL-1b [19]. This may explain the cartilage protective effects of diacerein observed in animal models of OA [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the post-membrane level, diacerein inhibits the release of inflammatory and cartilage-degrading factors, inhibiting the activation of nuclear factor-kappa B [18]. It stimulates the production of cartilage growth factors such as transforming growth factor-beta and cartilage components, even in the presence of IL-1b [19]. This may explain the cartilage protective effects of diacerein observed in animal models of OA [20].…”
Section: Discussionmentioning
confidence: 99%
“…Rhein, the active metabolite of diacerein, has shown in vitro and in vivo the inhibition of the IL-1β, as well as the reduction of the collagenase production by joint chondrocytes, the reduction of fibrinolytic activity in synovial fluid [8,9] and the stimulation of the production of cartilage growth factors [10]. This way of action turned diacerein into an interesting option for the treatment of OA without the side effects of NSAIDs [11].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on lapine chondrocytes have shown that diacerein can inhibit collagenase production and modulate IL-1 inhibition of proteoglycan (PG) synthesis [6]. In addition, diacerein has been implicated in the regulation of transforming growth factor (TGF) β1 and β2 in articular chondrocytes [7]. To our knowledge, no clinical study has focused on fundamental aspects; at variance, findings in different models of OA were reported recently.…”
Section: Introductionmentioning
confidence: 99%